2021
DOI: 10.1051/0004-6361/202141129
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new nearby globular cluster with extreme kinematics located in the extension of a halo stream

Abstract: Context. We report the discovery of VVV-CL160, a new nearby globular cluster (GC) with extreme kinematics, located in the Galactic plane at l = 10.1477 deg, b = 0.2999 deg. Aims. We aim to characterize the physical properties of this new GC and place it in the context of the Milky Way, exploring its possible connection with the known GC NGC 6544 and with the Hrid halo stream. Methods. VVV-CL160 was originally detected in the VISTA Variables in the Vía Láctea (VVV) survey. We use the proper motions (PMs) from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…However, we also identify two old clusters (Patchick 125 and Patchick 126) that are located well inside the Galactic bulge. Their ages of 14 Gyr and > 8 Gyr, respectively, are inline with the results from previous works implying that the lower age limit for the MW bulge is ∼ 5 Gyr (e.g., Clarkson et al 2011) and the mean age is ∼ 10 Gyr (e.g., Freeman 2008), suggesting that the clusters are either real tenants of the bulge or, alternatively, intruders originating from the halo (e.g., Forbes & Bridges 2010; Massari et al 2019;Minniti et al 2021a;Romero-Colmenares et al 2021).…”
Section: Summary and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we also identify two old clusters (Patchick 125 and Patchick 126) that are located well inside the Galactic bulge. Their ages of 14 Gyr and > 8 Gyr, respectively, are inline with the results from previous works implying that the lower age limit for the MW bulge is ∼ 5 Gyr (e.g., Clarkson et al 2011) and the mean age is ∼ 10 Gyr (e.g., Freeman 2008), suggesting that the clusters are either real tenants of the bulge or, alternatively, intruders originating from the halo (e.g., Forbes & Bridges 2010; Massari et al 2019;Minniti et al 2021a;Romero-Colmenares et al 2021).…”
Section: Summary and Discussionsupporting
confidence: 89%
“…Significant effort has been devoted in the last years to studying the real nature of GC candidates and indeed many of them have been confirmed. A few examples are VVV-CL001 (Minniti et al 2011;Fernández-Trincado et al 2021b), VVV-CL002 and VVV-CL003 (Moni Bidin et al 2011), FSR 1716Minniti et al 2017b), RLGC 1 and 2 (Ryu & Lee 2018), Camargo 1107, 1108, and 1109(Camargo & Minniti 2019, FSR 1758 (Barbá et al 2019;Romero-Colmenares et al 2021), Garro 01 (Garro et al 2020), UKS 1 (Fernández-Trincado et al 2020), Patchick 99 (Garro et al 2021b), FSR 19 and FSR 25 (Obasi et al 2021), VVV-CL160 (Minniti et al 2021a), Minni 48 (Minniti et al 2021b), FSR 1776Dias et al 2021), Ton 1 (Fernández-Trincado et al 2021, in press), and other 9 GCs in Garro et al (2021c).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the VVV/VVVX survey has revealed that the census of Galactic GCs is still not complete, and more than 300 new low-luminosity GC candidates have been identified in the VVV/VVVX bulge+disc area toward the inner galaxy (see e.g. Minniti et al 2020Minniti et al , 2021b, bulge region (Minniti et al 2017a(Minniti et al ,b, 2018bCamargo & Minniti 2019;Palma et al 2019;Garro et al 2021b;Obasi et al 2021), disc region (Garro et al 2020), the extension of the Hrid halo stream (Minniti et al 2021a), and the Sagittarius system (Minniti et al 2021c;Garro et al 2021a). A few of those candidates have been confirmed as true GCs (Contreras Ramos et al 2018;Gran et al 2019;Barbá et al 2019;Villanova et al 2019;Gran et al 2021a;Romero-Colmenares et al 2021;Dias et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the population of old globular clusters in the Sagittarius (Sgr) dwarf galaxy has recently gained a renewed strength from the availability of new kinematic, optical and infrared photometric data sets (e.g. Alfaro-Cuello et al 2019;Bellazzini et al 2020;Arakelyan et al 2021;Minniti et al 2021a). We here revisited the recent work by Minniti et al (2021b) who discovered eight globular clusters in the main body of the Sgr dwarf galaxy.…”
Section: Introductionmentioning
confidence: 98%